S97. IS EARLY DEBUT OF SUBSTANCE USE ASSOCIATED WITH VIOLENT OFFENDING IN SCHIZOPHRENIA?. (18th May 2020) - Breivik Storvestre, Guttorm; Jensen, Arvid; Bjerke, Espen; Tesli, Natalia; Rosaeg, Cato; Lagerberg, Trine; Friestad, Christine; Andreassen, Ole A; Melle, Ingrid; Haukvik, Unn K
Abstract: Background: Substance use is one of many risk factors for schizophrenia, and substance use is also associated with violent offending. This study compared a group of individuals suffering from schizophrenia with a history of violent offending (SCZ-V) to a group of schizophrenia patients without any history of violent offending (SCZ-NV). We investigated whether there is a difference between the SCZ-V and SCZ-NV groups when it comes to lifetime use, and debut age for use, of alcohol, cannabis, and amphetamines. Methods: This study examined the overall lifetime substance-use and the debut age of use of alcohol, cannabis and amphetamine among a selected group of patients with schizophrenia and a history of violent offending (SCZ-V n=25) recruited from psychiatric security wards in South-Eastern Norway, compared to a matched group of schizophrenia patients without violent offending (SCZ-NV n=34). Participants completed interviews and questionnaires to confirm diagnoses and to map the history of substance use. Results: While we found no significant difference in lifetime use of alcohol and cannabis between the groups (alcohol: SCZ-V: 88%, SCZ-NV: 97%, cannabis: SCZ-V: 76%, SCZ-NV: 71%), the SCZ-V group reported significantly more lifetime use of amphetamines compared to the SCZ-NV group (SCZ-V: 76% vs SCZ-NV: 18%, p<0.001). When comparing debut ages for substance use, the SCZ-V group was significantly younger than the SCZ-NV group at debut of alcohol (Mean age SCZ-V: 13.8 vs. SCZ-NV: 16.4, p=.004), cannabis (Mean age SCZ-V: 14.0 vs. SCZ-NV: 18.3, p<.001), and amphetamines (Mean age SCZ-V: 15.6 vs. SCZ-NV: 21.2, p=.001). Discussion: The SCZ-V group reported significantly more lifetime use of amphetamine and a significantly lower debut age for use of alcohol, cannabis, and amphetamines than the SCZ-NV group. According to the Norwegian Institute of Public Health, the average lifetime uses of cannabis for the general Norwegian population between 16 and 64 years old is 20.6%, while the average for the population between 16 and 34 years old when it comes to ever have used amphetamines is 4.7%. The numbers for both the SCZ-V and the SCZ-NV groups were noticeably higher than the population averages. What separates the groups are the significantly lower debut age of drug use in the SCZ-V group, and especially the higher number of lifetime amphetamines use. The findings point towards an association between the early debut of use of alcohol, cannabis, and amphetamines, and later violent offending in patients suffering from schizophrenia.